An Investigation of Geographic Mapping Techniques for Internet Hosts - Padmanabhan, Venkat; Subramanian, L. (ACM SIGCOMM 2001, 2001)
In this paper, we ask whether it is possible to build an IP address to geographic location mapping service for Internet hosts. Such a service would enable a large and interesting class of location-aware applications. This is a challenging problem because an IP address does not inherently contain an indication of location.We present and evaluate three distinct techniques, collectively referred to as IP2Geo, for determining the geographic location of Internet hosts. The first technique, Geo Track, infers location based on the DNS names of the target host or other nearby network nodes. The second technique, GeoPing, uses network delay measurements from geographically distributed locations to deduce the coordinates of the target host. The third technique, GeoCluster, combines partial (and possibly inaccurate) host-to-location mapping information and BGP prefix information to infer the location of the target host. Using extensive and varied data sets, we evaluate the performance of these techniques and identify fundamental challenges in deducing geographic location from the IP address of an Internet host.